2019
DOI: 10.24075/brsmu.2019.061
|View full text |Cite
|
Sign up to set email alerts
|

Brain connectivity changes in patients with working memory impairments with chronic ischemic cerebrovascular disease

Abstract: One of the methods of assessment of cognitive functions in patients with chronic ischemic cerebrovascular disease — CICD (dyscirculatory encephalopathy) implies studying connectivity of neural networks through the analysis of rest functional magnetic resonance imaging (rest fMRI) data. The main objective of this study was to assess the relationship between working memory (WM) characteristics and connectivity of various parts of the brain in patients diagnosed with CICD. The study involved 22 female CICD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The results indicate that an expected false discovery rate (FDR) of r-values is less than 5%. Previous studies also demonstrated that memory characteristics are related to brain network connectivity (Fokin et al, 2019;Vecchio et al, 2019). There were no significant differences in the LMWT scores or in the other cognitive tests that we applied in the carriers of PICALM AA&AG and PICALM GG genotypes.…”
Section: Discussionsupporting
confidence: 51%
“…The results indicate that an expected false discovery rate (FDR) of r-values is less than 5%. Previous studies also demonstrated that memory characteristics are related to brain network connectivity (Fokin et al, 2019;Vecchio et al, 2019). There were no significant differences in the LMWT scores or in the other cognitive tests that we applied in the carriers of PICALM AA&AG and PICALM GG genotypes.…”
Section: Discussionsupporting
confidence: 51%
“…There are many physiological markers of the body's response to stress agents, including limiting time factors. The parameters of these markers depend on the type of activity and the individual typological characteristics of the organism (Fokin, 2014). Numerous studies prove the fact of distinct individual differences in people's resistance to stress under conditions of psychoemotional stress (Sudakov, 2005).…”
Section: Introductionmentioning
confidence: 99%